The role of the family in the lives of children with SEN - Lupea, Cristina; Rus, Mihaela; Sandu, Mihaela Luminița; Rus, Ciprian Vasile (Technium Social Sciences Journal, 2024)
The choice of this topic is motivated by the crucial relevance of family support in the context of the development of children with Special Educational Needs (SEN). In the current educational paradigm, the family is an essential nucleus in facilitating the cognitive, emotional and social progress of these children. The contribution of the family in building a strong foundation of support and motivation can decisively influence the developmental path and social integration of children with ESD. It is therefore imperative to explore in depth the function of the family in the context of these children's lives, as the literature has consistently illustrated the beneficial impact of family involvement on their social, emotional and academic development. Families are catalytic agents in promoting self-confidence, autonomy and adaptability, as well as being a vital support in navigating the intrinsic challenges associated with ASD. This study aims to deepen our understanding of family dynamics and their essential contribution to the education of children with ASD, recognizing the central role they play in shaping their educational and social trajectories. Adopting a holistic perspective in the education of children with ESD requires a synergy between the family, educational institutions and professionals from various fields. A detailed understanding of the role and contribution of the family can facilitate the development of optimised educational strategies and the setting of convergent educational goals aimed at holistically supporting children's development. In addition, the family is a fundamental pillar in promoting the social integration and inclusion of children with ESC. Through family networks, children are supported in developing social skills, establishing interpersonal links and actively participating in community initiatives. This underlines the need for an integrated approach, where family, school and community work closely together to ensure an inclusive and developmental environment for children with SEN.